Sexual violence against men in Brazil: underreporting, prevalence, and associated factors - Ferreira, Denis Gonçalves; Bortoli, Maritsa Carla de; Pexe-Machado, Paula; Saggese, Gustavo Santa Roza; Veras, Maria Amelia (Revista de Saúde Pública, 2023)
OBJECTIVES: Identifying and mapping the literature regarding sexual violence against Brazilian boys and men, as well as describing its underreporting, prevalence, and associated factors. METHODS: We conducted a scoping review by searching PubMed, Biblioteca Digital Brasileira de Teses e Dissertações, Biblioteca Virtual em Saúde, Scopus, and Web of Science databases. The inclusion criteria were: (a) surveys including data on sexual violence; (b) inclusion of boys or men as victims of sexual violence; (c) presenting statistical data on prevalence, underreporting, and factors associated with sexual violence among Brazilian boys and men. RESULTS: We found a total of 1,481 papers. Ultimately, 53 were included and had their data extracted. Most studies are quantitative in nature (n = 48). The total number of participants across studies was 1,416,480 and the prevalence of sexual violence ranged from 0.1% to 71%. It is important to note that underreporting statistical data was cited in several studies. The group with the highest prevalences was men who have sex with men and those with sexual dysfunctions. Increased tendency to drug use, social isolation, unprotected anal sex, suicidal ideation, sexual dysfunction, and post-traumatic stress disorder were statistically significant predictors for having experienced sexual violence. CONCLUSIONS: Despite the prevalence of sexual violence being high against Brazilian boys and men, this area of is surprisingly understudied and there are few studies with this exclusive scope. Social cultural issues, such as sexism, contribute to the underreporting of sexual violence. Additionally, we identified issues related to mental, sexual and reproductive health to be associated with sexual violence. Based on our findings, we recommend the implementation and development of a structural infrastructure aimed at supporting boys and men who are victims of sexual violence, and preventing negative outcomes for this affected group.